Artificial fluorescent phosphatase enzyme - Mariz, Beatriz de Pina (2022)
Enzymes are extremely complex molecular machines which catalyse with great efficiency a wide range of chemical reactions. Its catalytic efficiency is, however, limited to certain conditions such as temperature, solvent and pH. Artificial enzymes are designed to catalyse non-natural reactions or reactions for which they are not naturally predisposed. Given the complexity of these biomolecules, the development of an artificial enzyme is a very demanding process. In this work it is proposed the development of an artificial fluorescence phosphatase enzyme PM-GFP that comprises the PM motif, fused to green fluorescent protein (GFP), the most well-known reporter protein. Here we show that PM-GFP presents catalytic activity for 1 μM enzyme, 10 mM pNPP substrate at 37 ºC and 45 ºC presenting a rate of 0.24 min-1 for the best condition.PM-GFP was recombinantly expressed using E. coli as the host organism. The soluble fraction was purified by chromatography-based techniques with 99% purity and the insoluble fraction was solubilized and purified by matrix-assisted refolding on-column with 100% purity.The catalytic activity associated with the PM-GFP stability makes this artificial fluorescent protein a suitable alternative to the chemical catalysts and for biomedical applications, such as enzyme replacement therapies.